Primary prevention efforts are poorly developed in people at high cardiovascular risk: A report from the European Society of Cardiology EURObservational Research Programme EUROASPIRE V survey in 16 European countries - Kotseva, Kornelia; De Backer, Guy; De Bacquer, Dirk; Rydén, Lars; Hoes, Arno; Grobbee, Diederick; Maggioni, Aldo; Marques-Vidal, Pedro; Jennings, Catriona; Abreu, Ana; Aguiar, Carlos; Badariene, Jolita; et al. (European journal of preventive cardiology, 2021)
BACKGROUND: European Action on Secondary and Primary Prevention by Intervention to Reduce Events (EUROASPIRE) V in primary care was carried out by the European Society of Cardiology EURObservational Research Programme in 2016-2018. The main objective was to determine whether the 2016 Joint European Societies' guidelines on cardiovascular disease prevention in people at high cardiovascular risk have been implemented in clinical practice. METHODS: The method used was a cross-stional survey in 78 centres from 16 European countries. Patients without a history of atherosclerotic cardiovascular disease either started on blood pressure and/or lipid and/or glucose lowering treatments were identified and interviewed ≥ 6 months after the start of medication. RESULTS: A total of 3562 medical records were reviewed and 2759 patients (57.6% women; mean age 59.0 ± 11.6 years) interviewed (interview rate 70.0%). The risk factor control was poor with 18.1% of patients being smokers, 43.5% obese (body mass index ≥30 kg/m2) and 63.8% centrally obese (waist circumference ≥88 cm for women, ≥102 cm for men). Of patients on blood pressure lowering medication 47.0% reached the target of <140/90 mm Hg (<140/85 mm Hg in people with diabetes). Among treated dyslipidaemic patients only 46.9% attained low density lipoprotein-cholesterol target of <2.6 mmol/l. Among people treated for type 2 diabetes mellitus, 65.2% achieved the HbA1c target of <7.0%. CONCLUSION: The primary care arm of the EUROASPIRE V survey revealed that large proportions of people at high cardiovascular disease risk have unhealthy lifestyles and inadequate control of blood pressure, lipids and diabetes. Thus, the potential to reduce the risk of future cardiovascular disease throughout Europe by improved preventive cardiology programmes is substantial.
Keywords: mužské pohlaví; Male; senioři; Humans; Female; lidé; Middle Aged; ženské pohlaví; lidé středního věku; Evropa; rizikové faktory kardiovaskulárních chorob; kardiologie; kardiovaskulární nemoci; rizikové faktory; Diabetes Mellitus, Type 2; Heart Disease Risk Factors; Europe; Risk Factors; primární prevence; diabetes mellitus 2. typu; Aged; Primary Prevention; Cardiology; Cardiovascular Diseases